O tratamento dos espaços livres em uma cidade média planejada: o caso de Ipatinga/MG - Fabiana Correia Dias (2011)
This dissertation deals about the open spaces on the city of Ipatinga/MG with reference to the design and construction of the Usiminass Company Town. The view of research has been done since the project design and its establishment until the landscape produced in five decades with its urban growth. Such expansion, linked to income opportunities, is the result of actions taken by both the private and the state or municipal government. For this, analyses the environmental and urban policies that could serve the permanence of the open spaces of the city, including those idealized by the architects Hardy Raphael Filho and Marcelo Bhering in the Urban Plan of the Usiminass Company Town in 1958. The open spaces and adaptation to the natural land of urban form were object of attention in the plan of 1958, acting as "green curtain" to curb air, noise and visual pollution of factory. It was found that the occupation after the Company Town also tried to adapt to propitious land to urbanization. There remained, then, as open space those areas of high slopes located north of the city, those along the Ipanema river that formed a complex linear park and those that relate to green belt of Usiminas. It was found also that the open spaces were not recognized as vital to the quality of urban life in the last revision of municipal master plan in 2006. This legal instrument presented a guideline defining these spaces as areas of urban expansion, which was embargoed by the intervention of the prosecutor specializing in the environment. Prosecutors considered those essential for the continuity of the industry activities within the urban fabric, thus fulfilling the social function of land. It is intended with this work contribute to the expansion of interdisciplinary theoretical reference on the subject and the city. Also aims to strengthen the conceiving of a sustainable urban landscape and without risk to the phenomena of impact intended or accidental, and thus increase access to open spaces as a citizen's right to the city and to the environment.